2009
DOI: 10.1007/s11325-009-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allopurinol on cardiac function and oxidant stress in chronic intermittent hypoxia

Abstract: ALLO is associated with improvement in CIH-associated oxidant stress, myocardial dysfunction, and apoptosis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…In this context, for preventing harmful effects of oxidative stress, many antioxidant agents, such as vitamin E, melatonin, retinol, β-carotene, omega-3, resveratrol, allopurinol, melatonin, Nacetylcysteine, zinc aspartate, and caffeic acid phenethyl ester, vitamin C, coenzyme Q10, and acetylcysteine have been used with different success rates. [46][47][48][49][50] Although numerous experimental animal studies have confirmed the efficacy of antioxidants in reducing short-term damaging effects of testicular torsion, different antioxidant agents have been investigated to reduce the short-and long-term reperfusion damage on the testes. Anti-apoptotic, anti-inflammatory, and antioxidant properties of oxytocin have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, for preventing harmful effects of oxidative stress, many antioxidant agents, such as vitamin E, melatonin, retinol, β-carotene, omega-3, resveratrol, allopurinol, melatonin, Nacetylcysteine, zinc aspartate, and caffeic acid phenethyl ester, vitamin C, coenzyme Q10, and acetylcysteine have been used with different success rates. [46][47][48][49][50] Although numerous experimental animal studies have confirmed the efficacy of antioxidants in reducing short-term damaging effects of testicular torsion, different antioxidant agents have been investigated to reduce the short-and long-term reperfusion damage on the testes. Anti-apoptotic, anti-inflammatory, and antioxidant properties of oxytocin have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…IH is characterized as cyclic episodes of hypoxia of short duration followed by normoxia [4], leading to increased generation of intracellular reactive oxygen species (ROS) during re-oxygenation following hypoxia [5]. Previously, excess ROS accumulation was itself considered injurious because it can cause lipid peroxidation, protein oxidation, DNA damage [6] and intracellular ion deregulation [7], damaging cellular physiological function. However, it is generally accepted at present that ROS may exert beneficial actions [8] because short or moderate durations of ROS generation can result in pre-conditioning protection of the heart [9] against ischemia/reperfusion (I/R) injury [1].…”
Section: Introductionmentioning
confidence: 99%
“…IH-induced cellular damage is related to the increase in intracellular reactive oxygen species (ROS) generated during reoxygenation after hypoxia and the attenuation of antioxidant enzyme capacity (Carpagnano et al 2003;Park and Suzuki 2007). Moreover, IH may cause lipid peroxidation (Chen et al 2005;Williams et al 2010), protein oxidation and DNA damage (Chen et al 2008), thus reducing cardiomyocyte numbers by apoptosis and necrosis, resulting in ventricular dysfunction (Chen et al 2005). This condition causes cardiomyocyte injury similar to that caused by ischaemiareperfusion (IR) injury (Dong et al 2003;Guo et al 2009).…”
Section: Introductionmentioning
confidence: 99%